Radioembolization for the treatment of hepatocellular carcinoma - Kim, Hyo-Cheol (Clin Mol Hepatol, 2017)
Transarterial radioembolization (TARE) with yttrium 90 ((90)Y), an intra-arterial procedure performed by interventional radiologists, has begun being utilized in managing hepatocellular carcinoma (HCC) in Korea. There are two available TARE products: glass and resin microspheres with different physical characteristics. All patients undergoing TARE must be assessed with clinical examination and laboratory tests as well as a thorough angiographic evaluation. TARE is safe and effective in the treatment of unresectable HCC, as it has longer time-to-progression, greater ability to downsize tumors for liver transplantation, less post-embolization syndrome, and shorter hospitalization compared with chemoembolization. TARE can also serve as an alternative to ablation, surgical resection, portal vein embolization, and sorafenib. The utility of TARE continues to expand with new insights in interventional oncology.